Structure And Properties of Thick Layer Polymer Materials - Kholmominov Abdulfatto Axatovich; Yodgorov Shoxrux Khursan ogli; Nazarov Bekzod Jumayevich (Zien Journals, 2022)
Thin polymeric materials are generally understood to be flat, film-like or paper-like nonwoven materials with a thickness of nanometers to millimeters, and these materials are widely used in practice. Today, such materials include polymer films, natural and synthetic fibers
Keywords: Polymer; polyethylene film; silk cocoon; fibroin